Uji Aktivitas Klorofil Daun Putri Malu (Mimosa pudica Linn) Sebagai Antibakteri Terhadap Bakteri Staphylococcus aureus dan Escherichia coli - Annisa Rahmah; Idramsa; Iin Agustina Ritonga (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
Infectious diseases caused by pathogenic bacteria such as Staphylococcus aureus and Escherichia coli remain a health problem, especially due to increasing antibiotic resistance. Therefore, antibacterial alternatives from natural materials are needed, one of which is the chlorophyll pigment from Mimosa pudica Linn. This study aims to test the antibacterial activity of chlorophyll from young and old leaves of M. pudica Linn and compare the inhibitory power of both against test bacteria. This study is an experimental study that includes the preparation of simple drugs, ethanol extraction, liquid-liquid fractionation, purification using thin layer chromatography (TLC) and column chromatography, and antibacterial testing by disc diffusion method using standard bacterial inoculum McFarland 0.5. The purification results showed an Rf value of 0.87 with one spot indicating pure chlorophyll fraction. The antibacterial activity of chlorophyll is relatively weak, but the chlorophyll fraction of old leaves showed greater inhibitory power than young leaves. The highest inhibition zone against S. aureus was obtained from old leaf chlorophyll of 4.00 ± 1.01 mm, while against E. coli it was 2.54 ± 0.52 mm.